The invasion of heaven - Koep, Michael B. (Koep, Michael B. Newirth mythology, 2013)
The first part of the Newirth trilogy is mystery, adventure, myth, betrayal, murder and madness. Psychologist Loche Newirth wonders if it was his fall: the fifty foot drop from the rocky cliff to the icy water below. Is this why he has been hallucinating? Or is it because one of his cients is dead, or his mentor has gone mad, or that his wife is leaving him?